Parent use of onomatopoeia: a way to facilitate language learning or just something we do? - Lowe, Tracy (The University of Edinburgh, 2013)
Research has shown children’s early productive vocabulary to be largely onomatopoeic (Tardif, Fletcher, Kaciroti, Liang, Zhang, & Marchman, 2008; Caselli, Casadio, & Bates, 2001). However, existing research has not addressed or documented why children exhibit this early production bias towards onomatopoeic, or sound symbolic words. In order to effectively study the productive vocabulary of children, it may be important to consider lexical input, in order to understand if there is a link between what the child hears in their input and the types of words they produce. As children exhibit an early onomatopoeic bias, the study of onomatopoeia can help to determine if children have a preference for these words or rather if they are exposed to an excessive amount of onomatopoeic in their input. The goal of this study is to examine parent use of onomatopoeia, as a way of potentially explaining children’s early bias towards these words.
Keywords: sound symbolism; onomatopoeia